Evaluasi sensori dan resistensi es krim jagung kelor dengan penstabil yang berbeda - Kamilla Riska Tiastuti; Mohammad Jusuf Randi; Yan El Rizal Unzilatirrizqy Dewantoro (Journal of Food and Agricultural Product, 2023)
This study aims to evaluate the sensori, pH, sugar content, and melting properties of ice cream made from a mixture of corn and moringa leaves with the addition of alginate stabilizer, CMC, and gelatin. This study used a completely randomized design (CRD) in one direction, where the main factor was the type of stabilizer (alginate, carboxymethylcellulose, and gelatin). The parameters of this study were pH, sugar content, melting, and organoleptic. The gelatin stabilizer increased the pH of the ice cream but was lower than the alginate stabilizer, which showed a significant difference. The addition of a CMC stabilizer increases the sugar content of ice cream significantly. Although the use of CMC or gelatin stabilizer was not significant in reducing the melting of ice cream, the use of alginate stabilizer gave the best texture, followed by no stabilizer, CMC, and gelatin. There are significant differences in the texture and color of ice cream, but no significant differences in aroma or taste. In conclusion, the use of alginate stabilizer affected the texture and color of Moringa corn ice cream, while the aroma and taste were not significantly affected. Keywords: ice cream, corn, moringa leaves, stabilizer, alginate, CMC, gelatin, sensori, melting